PENGARUH AIR LIMBAH CELUPAN BATIK DI PARAKANNYASAG TASIKMALAYA TERHADAP PERTUMBUHAN KI APU (Pistia stratiotes L.) - Tri Cahyanto; Tony Sudjarwo Sudjarwo; Rida Widayanti; Mar’atus Shalikha (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2017)
Batik industry produces waste water containing chromium which can be harmful for ecosystem and human health. There had been research aimed to find out the influence of batik dye waste water in Parakannyasag Tasikmalaya on the growth of Pistia stratiotes L. Material of P. stratiotes was obtained from Indihiang rice field, Tasikmalaya. Waste water was taken from disposal of home batik dye industry in Parakannyasag Tasikmalaya. Study design used a Complete Randomized Design (RAL) with 5 treatments (0%, 25%, 50%, 75% and 100%) and 5 replications. The growth parameter include root length, leaf number, leaf length, leaf width, leaf broad, stolon number, stolon length, fresh weight and calculated of Relative Growth Rate (RGR), Doubling Time (DT) and leaf chlorophyll content were observed, The result showed growth of P. stratiotes at 25% concentration of wastewater was root length 2,2 cm, leaf number 3,5 strands, leaf length 0,3 mm, leaf width 0,4 mm, leaf broad 1,7 mm, stolon number 1,3 pieces, stolon length 1,8 cm and fresh weight 4,4 g; At 50% consentration of waste water showed root length 11,2 cm, leaf number 5,7 strands, leaf length 0,39 mm, leaf width 0,17 mm, leaf broad 1,3 mm, stolon number 1,6 pieces, length of stolon 2,6 cm and fresh weight 3,6 g. At 75% of waste water consentration showed, root length 5,5 cm, lef number4,8 strands, leaf length -0,1 mm, leaf width 0,1 mm, leaf broad -0,4 mm, stolon number 1,1 pieces, stolon length 2,0 cm and fresh weight 3,0 g; At 100% consentration of waste water showed root length 6,6 cm, leaf number 3,8 strands, leaf length -0,3 mm, leaf width -0,2 mm, leaf broad -0,5 mm, stolon number 0,9 pieces, length 1,9 cm stolon and fresh weight 2,9 g. The highest RGR value at 25% of wastewater concentration demonstrated 0,02 g/day and the highest DT value at 75% concentration of waste water demonstrated 48,0 days. The highest growth of root organs occured at 50% concentration of waste water and caused in optimum growth of P. stratiotes.